En mobilstrategis komponenter - Aasa, Martin; Hällström, Alexander (2015)
This bachelor thesis has been produced by the initiative of Luleå municipality, with the focus investigating the content of a mobile strategy. In this thesis, we tried to distil the important aspects of a mobile strategy. The purpose was to study which aspects should or could be part of a mobile strategy. With the help of a theoretical review of the areas: IT-strategy, strategy, mobile strategy, Bring Your Own Device, Mobile device management also Luleå municipalities IT-policy and their IT-Strategy, we produced a theoretical framework. This framework, together with a survey and semi-structured interviews, form the base of the study. The survey consisted of a total of 194 respondents, which corresponds to 3% of the total amount of the employees, and we did 7 interviews with 7 different IT-coordinators on different units. The result shows that a mobile strategy needs to consider following aspects: Bring Your Own Device, Choose Your Own Device, Management system, Technology neutrality, Application management, Stress management, and Overview of fixed telephony. Validerat; 20151017 (global_studentproject_submitter)